Preoperative radiotherapy with concomitant fluoropyrimidine-based chemotherapy for resectable locally advanced rectal cancer [Rezeke edilebilir lokal ileri evre rektum kanserinde floroprimidin bazli kemoterapi ile eş zamanli ameliyat öncesi radyoterapi] - (:unkn) unknown (My University, 2008)
OBJECTIVES: To investigate the treatment results and tumor and patient characteristics in patients with resectable locally advanced rectum cancer (LARC) who were treated with preoperative chemoradiation. METHODS: T3/T4 rectal adenocarcinoma patients (n=50) were evaluated retrospectively. Tumors were located within 5 cm of the anal verge in 60% of patients. Twenty-four (48%) of the patients had positive lymph nodes. Pelvic radiotherapy was administered with a median dose of 45Gy in linear accelerator. Concurrent fluoropyrimidine was given orally (n=18) or intravenously (n=32). RESULTS: Median follow-up was 17 months. Two-year local control, disease-free survival and overall survival were 93.6%, 90.3% and 93.3%, respectively. Sphincter-preserving surgery rate was 43% for distal tumors. Downstaging was observed in 35% with seven ypT0N0 cT4 (p=0.01), lymphovascular-perineural invasion (p=0.01) and pN+ (p=0.02) were predictive for a worse prognosis. Grade 3 toxicity was observed in 8% of patients. CONCLUSION: Preoperative chemoradiotherapy demonstrated similar benefit regarding sphincter preservation with that of standard postoperative multimodality therapies in LARC patients.
Keywords: Chemoradiotherapy; Neoadjuvant treatment; Rectal cancer; Turkish patients